The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1055/s-0029-1241729
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Neonates with Gastroschisis in U.S. Children's Hospitals

Abstract: Our objectives are to report patient characteristics, comorbidities, and outcomes for gastroschisis patients and analyze factors associated with mortality and sepsis. Using Pediatric Health Information System data, we examined neonates with both an International Classification of Diseases, 9th Revision diagnosis (756.79) and procedure (54.71) code for gastroschisis (2003 to 2008). We examined descriptive characteristics and conducted multivariate regression models examining risk factors for mortality, during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 23 publications
1
48
0
9
Order By: Relevance
“…Gastroschisis represents an asymmetrical abdominal wall defect localized to the right of an intact umbilicus with viscera herniation. Unlike omphalocele, gastroschisis represents an isolated defect without associated anomalies, although around 10% of the cases are complicated by bowel atresia [7]. Epidemiologic studies have shown that chromosome abnormalities and single gene disorders are rarely associated with gastroschisis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Gastroschisis represents an asymmetrical abdominal wall defect localized to the right of an intact umbilicus with viscera herniation. Unlike omphalocele, gastroschisis represents an isolated defect without associated anomalies, although around 10% of the cases are complicated by bowel atresia [7]. Epidemiologic studies have shown that chromosome abnormalities and single gene disorders are rarely associated with gastroschisis [8].…”
Section: Discussionmentioning
confidence: 99%
“…but the mortality rate reported in our study (11.7%) tallies with the values reported in most studies. Prematurity, intrauterine growth retardation and the presence of a congenital circulatory or pulmonary anomaly are external factors associated with a poorer outcome for children born with GS [3] . In our study, three babies (3/68) showed concomitant fetal abnormalities incompatible with life; finally, five babies died from GS and associated bowel complications (5/68, 7.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged TPN, with its risk of sepsis, is directly related to intestinal recuperation, and the morbidity of GS is closely related to intestinal damage [20] . While gastrointestinal complications such as matting between the loops, malrotation, volvulus, perforations and atresia increase the complexity of early management [19,21] , later management may be complicated by the presence of problems of absorption, intestinal dysmotility, obstruction, NEC, infarction and stenosis [1,3,9] . The pathogenesis of secondary bowel lesions is not fully understood, but both chemical and mechanical origins are concerned [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В этой научной работе также установлено, что у детей с «осложненным гастрошизисом» в 6 раз чаще развиваются заболевания печени, вследствие длительного паренте-рального питания. В другом исследовании отмечены вы-сокая частота развития катетер-ассоциированного сепси-са, длительное время до перехода на энтеральное питание и увеличение длительности госпитализации больных с атрезией и некрозом кишечника [71]. Гастрошизис по-прежнему является наиболее частой причиной транс-плантации кишечника у детей [72].…”
Section: гастрошизисunclassified